2009
DOI: 10.1111/j.1365-2893.2009.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous blood donor screening indicated a lower prevalence of viral hepatitis in East vs West Germany: epidemiological benefit from established health resources

Abstract: Prevalence data concerning viral hepatitis and human immunodeficiency virus (HIV) in the general population are usually scarce. We aimed for a large cohort representative of the general population that required little funding. Autologous blood donors are relatively representative of the general population, and are tested for viral hepatitis and HIV in many countries. However, frequently these data are not captured for epidemiologic purposes. We analysed data from well over 35,000 autologous blood donors as rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
(11 reference statements)
1
12
1
Order By: Relevance
“…Two other German studies both performed in the Western part of Germany showed higher prevalences of 1.4% (95% CI 0.84–2.42) and 1.59% (95% CI 1.3–1.96) HBsAg carriers, respectively [2,3]. This difference is however in line with other data regarding differences in the prevalence of HBV in the Western and Eastern part of Germany [1,4]. Importantly, the prevalence of HBV among German-born women was much lower with 0.2%, while it was 9.1% in women born in Asia, in line with the elevated prevalences found in populations of the Far East of up to 10% among all pregnant women [11].…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Two other German studies both performed in the Western part of Germany showed higher prevalences of 1.4% (95% CI 0.84–2.42) and 1.59% (95% CI 1.3–1.96) HBsAg carriers, respectively [2,3]. This difference is however in line with other data regarding differences in the prevalence of HBV in the Western and Eastern part of Germany [1,4]. Importantly, the prevalence of HBV among German-born women was much lower with 0.2%, while it was 9.1% in women born in Asia, in line with the elevated prevalences found in populations of the Far East of up to 10% among all pregnant women [11].…”
Section: Discussionsupporting
confidence: 41%
“…In Germany the estimated prevalence of chronic hepatitis B is about 0.6%, whereas 7% of the population show markers of a subsided infection [1], with lower rates in the Eastern part versus the Western part of Germany. Furthermore, HBV prevalence is higher in immigrants from high-endemic regions [2,3,4]. In Europe, women are routinely screened for HBsAg during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In Saxony, up to 23% of the general population consume alcohol at a harmful level . In contrast, the prevalence of chronic viral hepatitis B and C in Eastern parts of Germany is low, and significant lower than in matched control groups from Western Germany …”
Section: Discussionmentioning
confidence: 71%
“…Recent findings suggest that HCV seroprevalence rates in Germany vary significantly by region, with higher prevalence rates in Western Germany compared to Eastern Germany and in urban versus rural areas [19], [20]. These regional variations may have direct implications for federal and local public health measures regarding prevention and control of HCV infection.…”
Section: Discussionmentioning
confidence: 99%